Recent Progress in Microfluidic Models of the Blood-Brain Barrier - Jiang, Lili (Micromachines (Basel), 2019)
The blood-brain barrier (BBB) is a critical physical and chemical barrier that maintains brain homeostasis. Researchers in academia and industry are highly motivated to develop experimental models that can accurately mimic the physiological characteristics of the BBB. Microfluidic systems, which manipulate fluids at the micrometer scale, are ideal tools for simulating the BBB microenvironment. In this review, we summarized the progress in the design and evaluation of microfluidic in vitro BBB models, including advances in chip materials, porous membranes, the use of endothelial cells, the importance of shear stress, the detection specific markers to monitor tight junction formation and integrity, measurements of TEER and permeability. We also pointed out several shortcomings of the current microfluidic models. The purpose of this paper is to let the readers understand the characteristics of different types of model design, and select appropriate design parameters according to the research needs, so as to obtain the best experimental results. We believe that the microfluidics BBB models will play an important role in neuroscience and pharmaceutical research.